A direct assessment of creep life based on small punch creep test. (December 2019) - Kim, Jeong Hwan; Ro, Uijeong; Lee, Hoomin; Kang, Seok Jun; Lee, Byung Ho; Kim, Moon Ki
Highlights: Two direct creep life assessment will be introduced for SPCT. Equivalent formulation are proposed to convert multiaxial state into uniaxial. A correction factor is defined to account for friction effect on contact surface. A case study successfully demonstrates the proposed method in comparison with UCT results. Abstract: The uniaxial creep test (UCT) has generally been used to identify creep properties of materials. However, it consumes an enormous amount of testing time and requires a substantial specimen volume. The small punch creep test (SPCT) is introduced as an alternative test method to overcome the shortcomings of the UCT. It uses a fingernail-sized sheet as a specimen (10 × 10 × 0.5 mm 3 ) and a spherical punch ball to apply load to the specimen. Despite these positive aspects, SPCT has rarely received much attention in industrial fields due to a complex interpretation process that requires additional processes such as UCT, FEM, and CEN code. In this paper, a direct assessment method for SPCT is proposed to evaluate creep life directly from the SPCT. In this method, a stress formulation was derived to convert force into one equivalent stress. Moreover, a non-dimensional correction factor was defined to consider the friction effect between the punch ball and specimen. To demonstrate this method, STS316L stainless steel was used as a test specimen for both the UCT and SPCT at 650 °C. A comparison of Larson-Miller models derived from each test result showed good reliability of the proposed direct assessment method.